Novel NG2‐CreERT2 knock‐in mice demonstrate heterogeneous differentiation potential of NG2 glia during development. Issue 6 (28th February 2014) - Huang, Wenhui; Zhao, Na; Bai, Xianshu; Karram, Khalad; Trotter, Jacqueline; Goebbels, Sandra; Scheller, Anja; Kirchhoff, Frank
<x xml:space="preserve">Abstract</x> NG2 (nerve/glia antigen‐2) is a type I transmembrane glycoprotein and also known as chondroitin sulfate proteoglycan 4. In the parenchyma of the central nervous system, NG2‐expressing (NG2+) cells have been identified as a novel type of glia with a strong potential to generate oligodendrocytes (OLs) in the developing white matter. However, the differentiation potential of NG2 glia remained controversial, largely attributable to shortcomings of transgenic mouse models used for fate mapping. To minimize these restrictions and to more faithfully mimic the endogenous NG2 expression in vivo, we generated a mouse line in which the open reading frame of the tamoxifen‐inducible form of the Cre DNA recombinase (CreERT2) was inserted into the NG2 locus by homologous recombination. Results from this novel mouse line demonstrate that at different developmental stages of the brain, NG2+ cells either stayed as NG2 glia or differentiated into OLs during the whole life span. Interestingly, when Cre activity was induced at embryonic stages, a significant number of reporter+ astrocytes could be detected in the gray matter after birth. However, in other brain regions, such as olfactory bulb, brain stem, and cerebellum, all of the NG2 glia was restricted to the OL lineage. In addition, tamoxifen‐sensitive and NG2 gene locus‐dependent gene recombination could be detected in a small, but persistent population of cortical NeuN+ neurons starting from the second postnatal week. GLIA 2014;62:896–913